"Normality": concept of how many faces? - Cláudia Rodrigues de Freitas (Universidade Federal de Santa Maria (UFSM), 2012)
This paper is intended to analyze how the concept of "normality", divided in normal and abnormal, has been taking shape in our time, based on Canguilhem's and Foucault's views. By analyzing the theory, I recognize evidence of a process of biologization of life which revisits itself and takes new shapes over the last years through the process of medicalization. Medicalization is the current controlling device and cannot be boiled down to prescribing medication, but we can also think of it as a gear, as a machine that transforms life into objects. As evidence of this analysis, a school situation intended to illustrate the concepts addressed is presented. The aforementioned situation was observed at the Municipal School System of Porto Alegre. Scholastic discourse generates different ways of acting and living in the school, but is it intended to do so?